A new dye‐modified poly(ethylene oxide)–poly(propylene oxide) polymer used as a dispersant for CI Disperse Red 60. (7th June 2013) - Zhang, Bin; Dong, Xia; Xuan, Jian; He, Jinxin
<x xml:space="preserve">Abstract</x> A new dye‐modified poly(ethylene oxide)–poly(propylene oxide) polymer, in which the dye molecule (CI Disperse Red 60) is bonded onto polyether monoamine via a triazine ring, was synthesised for the preparation of dye aqueous dispersions and was characterised by Fourier Transform‐infrared spectroscopy, 1H nuclear magnetic resonance spectroscopy and elemental analysis. This polymer exhibits unique dispersing performance for CI Disperse Red 60. The mechanism behind the improved performance is briefly discussed with the help of adsorption isotherms. The results indicated that the hydrophobic dye group of this polymer can strongly adsorb onto the dye particle surface through π–π interaction while its long hydrophilic poly(ethylene oxide) chains allow the formation of a thick layer around the dye particles. It was speculated that the adsorbed polymer molecule on the dye surface would form a brush‐like monolayer conformation. The dyeing performance of the prepared dye dispersions on polyester fabrics was also investigated. It was found that this polymer can effectively increase the apparent solubility of disperse dye. The dyed fabrics showed very good to excellent fastness to washing and rubbing, while the dyeing effluent was colourless.